Effective Learning Models: Advancing Islamic Education Materials for Quality Teaching and Learning - Hapriadi, Yusa Farhan; Zain, Irfan Ahmad (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2024)
The main issue found in this research is the lack of Islamic Religious Education material that can attract the attention of students and learners in PAI subjects. This research aims to find a new approach in developing Islamic Religious Education learning materials that suit the needs of students today. The main focus is divided into two aspects. First, includes the development of Islamic Religious Education learning materials which are based on the application of e-mobile based material models, second includes the development of Islamic Religious Education learning materials which are based on the application of Quipper School based material models. This research applies a qualitative approach, using the literature study method. The analytical approach used in this research is content analysis. Based on the study above, it can be concluded that the development of instrumental e-mobile-based PAI materials in the form of e-books which have been tested and the development of Islamic Religious Education learning materials based on Quipper School can be efficient and practical in its implementation in front of students, both directly and indirectly. . Both have proven effective in improving students' PAI learning achievement.